2010
DOI: 10.1007/s10055-009-0153-y
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality for assembly methods prototyping: a review

Abstract: Assembly planning and evaluation is an important component of the product design process in which details about how parts of a new product will be put together are formalized. A well designed assembly process should take into account various factors such as optimum assembly time and sequence, tooling and fixture requirements, ergonomics, operator safety, and accessibility, among others. Existing computer-based tools to support virtual assembly either concentrate solely on representation of the geometry of part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
145
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(149 citation statements)
references
References 99 publications
(94 reference statements)
0
145
0
4
Order By: Relevance
“…Moreover, Seth et al (2011) identified three main challenges that virtual assemblies must overcome to increase the level of realism: collision detection, inter-part constraint detection and PBM.…”
Section: Physics Simulation Enginesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Seth et al (2011) identified three main challenges that virtual assemblies must overcome to increase the level of realism: collision detection, inter-part constraint detection and PBM.…”
Section: Physics Simulation Enginesmentioning
confidence: 99%
“…Howard and Vance (2007) mentioned that a successful virtual assembly environment requires virtual parts to emulate real world parts behaviour. According to Seth et al (2011) this can be achieved by means of physics-based modelling (PBM), which uses physics simulation engines (PSEs) to simulate real world physics properties, such as friction, gravity and contact forces to perform the assembly. The use of PBM results in better appreciation and understanding of part functionality and can also lead to improved training of manual tasks (Wang et al, 2001;Zerbato et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…VR software is currently dominated by applications for entertainment and gaming purposes. Existing business or research data visualisation applications tend to be focussed on exploiting the VR environment for representation of spatial data such as engineering drawings, structures and mapping (Berg and Vance, 2016;Boulos et al 2017;Sastry and Boyd, 1998;Seth et al 2011). Within health and medical sciences VR is used for predominantly therapeutic or rehabilitation applications (e.g.…”
Section: Datashield Applications For Data Visualisationmentioning
confidence: 99%
“…et al 2011, Grajewski et al 2015), as well as in many other engineering activities, including simulations of machine operation and assembly (Pandilov et al 2015, Seth et al 2011), knowledge visualization (van Dam et al 2000, and configuration of variant products in the automotive branch , Jiang 2011. Virtual reality has many medical applications (Riva 2003) and is often used for educational purposes (Stansfield et al 2000).…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%